7 - Camwood (Pterocarpus Tinctorius) in the Political Economy of the Cross and Manyu Rivers Basin of Cameroon and Some Hinterland Communities, 1916-1961 - Henry Kam Kah, (Afrika Zamani, 2022)
Camwood exploitation and use played an important role in the political economy of the Cross and Manyu river basin of Cameroon and Nigeria including some hinterland communities throughout the era of British administration which spanned 1916-1961. The British occasionally intervened to end its unrestricted exploitation and regulated its commercialisation for the local and external market. In spite of their laborious effort in this direction, Camwood exploitation continued for various internal and external uses.